Method of automatic fault location in 6-35 kV electrical networks - Matsui, Anatolii; Shepel, Oleksandr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
The paper analyses the known means of fault location in electrical networks, identifies their disadvantages and proposes its own method of solving this problem. The model of electric network is built and investigated by MATLAB.